IMPLEMENTASI PROSES PEMUNGUTAN PAJAK AIR TANAH DI KOTA MALANG (STUDI PADA DINAS PENDAPATAN KOTA MALANG) - Riyanto, Inggar Ajeng Pradina (Jurnal Mahasiswa Perpajakan, 2014)
This research aims to know and describe the implementation  of  ground water tax collecting process in Malang city that conducted by Department of Regional Revenue of Malang City, the obstacles and the efforts undertaken to figure these obstacles. This research is descriptive approach. The focus of this research is the  implementation of ground water tax collecting processe, the obstacles and the efforts undertaken to figure these obstacles. Based on the results of research, the implementation of ground water tax collecting process in Malang city has been conducted in accordance with the definition of collection that was found in Law Number 28 Year 2009. But ground water tax collecting processes is not full-implemented to prevailing laws. The obstacles are lack of society’s awareness about their ground water tax obligations, the arrears, water meters have yet to be full-implemented, and ambiguity on commercial household. Efforts to figure obstacles are socialization and direct-approach to the society, collection in the  current month, water meters installation and increasing the price basic ground water. Key Word: Ground Water Tax, Tax Collecting, Regional Tax